2004
DOI: 10.1002/bit.20304
|View full text |Cite
|
Sign up to set email alerts
|

Monitoring of active but non-culturable bacterial cells by flow cytometry

Abstract: Flow cytometric signatures (i.e., light scatter, red and green fluorescence) were obtained for the active but non-culturable (ABNC) cells of E. coli and a coliform isolate H03N1, in seawater microcosms using BacLight, a live-dead assay kit from Molecular Probes (Eugene/Portland, OR). Previous studies have reported that there are two major adaptations, which cells undergo during the formation of ABNC states: cell wall toughening and DNA condensation. Therefore, we hypothesized that the matured ABNC forms should… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
45
0

Year Published

2005
2005
2020
2020

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 43 publications
(48 citation statements)
references
References 60 publications
3
45
0
Order By: Relevance
“…Under various stress conditions, many bacteria are able to enter a state where they are no longer culturable on standard media but still main- tain metabolic activity (3,5,7,18,24). As previously shown for other bacteria (23), the present results demonstrate for the first time that FCA is a valuable tool for characterizing VBNC cells of the Legionella genus. The 12 Legionella strains used in this study exhibited different heat inactivation curves as evaluated by FCA (Fig.…”
supporting
confidence: 85%
“…Under various stress conditions, many bacteria are able to enter a state where they are no longer culturable on standard media but still main- tain metabolic activity (3,5,7,18,24). As previously shown for other bacteria (23), the present results demonstrate for the first time that FCA is a valuable tool for characterizing VBNC cells of the Legionella genus. The 12 Legionella strains used in this study exhibited different heat inactivation curves as evaluated by FCA (Fig.…”
supporting
confidence: 85%
“…Several studies have successfully used LIVE/DEAD BacLight kit for the measurement of bacterial viability in environmental isolates (e.g., Haznedaroglua et al 2008;Portaels et al 2008). These observations, together with our earlier work conducted on osmotically stressed cultures of E. coli and coliform environmental isolate (H03N1) (Sachidanandham et al 2005), forecasted that no abnormalities in the staining of LIVE/DEAD BacLight kit in the viability measurements were observed (also see Fig. 5, live and dead cell count of Enterobacter sp.…”
Section: Flow Cytometric Analysis and Fluorescence-activated Cell Sorsupporting
confidence: 67%
“…Notably, it has been established that when starter cultures are subjected to various forms of sublethal stress, some cells may be injured and fail to grow on a medium adequate for the growth of unstressed cells, but they are capable of growth when they are given a suitable environment (6). Evidence of recovery of growth ability by damaged or injured, stressed cells by repairing or replacing damaged molecules under suitable conditions has been reported (3,29).…”
Section: Resultsmentioning
confidence: 99%
“…In this way, different cellular functions, such as reproductive growth, metabolic activity, and membrane integrity, can be detected, allowing a definition of the term viable-but-not-culturable cells (VBNC) (24) (other authors have called them active but nonculturable). Previous studies have reported that there are two major adaptations that cells undergo during the formation of VBNC states: cell wall toughening and DNA condensation (29). The detection of metabolic activity provides presumptive evidence of reproductive growth by the demonstration of enzyme activity, such as esterases, along with membrane integrity.…”
mentioning
confidence: 99%